Specific Volume and Antioxidant Activity of Gluten-Free Bread Based on Local Flour - Sani Dwiningrum Rahayu Br Ginting; Muhammad Fadhlillah; Safri Ishmayana (Universitas Pendidikan Ganesha, 2026)
Gluten-free bread is an important alternative for individuals with gluten intolerance or celiac disease. However, it still faces challenges in achieving a texture comparable to that of wheat-based bread and in its functional properties, especially its antioxidant activity. The use of local flour has potential as a solution but requires formulation optimization to achieve balanced physical and functional qualities. This study aims to analyze and optimize the combination of local flours in producing gluten-free bread with the highest specific volume characteristics and antioxidant activity. This study was an experimental study with a mixed design. The subjects included red rice flour, mung bean flour, and Cilembu sweet potato flour as the main ingredients of the formulation, with varying proportions based on the mixed design. The specific volume of bread (mL/g) and antioxidant activity (DPPH inhibition percentage) were then statistically analyzed to evaluate the effect of each component. The results showed that mung bean flour did not significantly affect specific volume or antioxidant activity. The two best formulations were obtained by combining red rice flour and Cilembu sweet potato flour. The formulation with a higher proportion of red riceflour produced the highest specific volume, 3.12 mL/g, with relatively lower antioxidant activity (3743%). In comparison, the formulation with a higher proportion of Cilembu sweet potato flour showed higher antioxidant activity (4636%) with a lower specific volume (2.58 mL/g). From this study, it can be concluded that the combination of red riceflour and Cilembu sweet potato flour has the potential to produce functional, gluten-free bread with physical and bioactive characteristics that add value using local ingredients.